2019
DOI: 10.1124/jpet.119.257600
|View full text |Cite|
|
Sign up to set email alerts
|

Quantitative Contribution of Six Major Transporters to the Hepatic Uptake of Drugs: “SLC-Phenotyping” Using Primary Human Hepatocytes

Abstract: Hepatic uptake transporters [solute carriers (SLCs)], including organic anion transporting polypeptide (OATP) 1B1, OATP1B3, OATP2B1, sodium-dependent taurocholate cotransporting polypeptide (NTCP), and organic anion (OAT2) and organic cation (OCT1) transporters, play a key role in determining the systemic and liver exposure of chemically diverse drugs. Here, we established a phenotyping approach to quantify the contribution of the six SLCs, and passive diffusion, to the overall uptake using plated human hepato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
93
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(97 citation statements)
references
References 53 publications
(88 reference statements)
1
93
0
Order By: Relevance
“…20%) to the systemic elimination, 20 and suggested involvement of other transporters in hepatic uptake. 27 Hence, the dynamic range of AUCR at high levels of hepatic OATP1B inhibition depends on the contribution of non-OATP1B-mediated clearance mechanisms even if they only make a small contribution (e.g., 10-20%) to overall clearance. This is the first demonstration that valsartan AUC 0-24h discriminated the dose-dependent effects of rifampicin as atorvastatin and pitavastatin did (Figure 2), although valsartan is not listed as clinical substrate for OATP1B (https ://www.fda.…”
Section: Discussionmentioning
confidence: 99%
“…20%) to the systemic elimination, 20 and suggested involvement of other transporters in hepatic uptake. 27 Hence, the dynamic range of AUCR at high levels of hepatic OATP1B inhibition depends on the contribution of non-OATP1B-mediated clearance mechanisms even if they only make a small contribution (e.g., 10-20%) to overall clearance. This is the first demonstration that valsartan AUC 0-24h discriminated the dose-dependent effects of rifampicin as atorvastatin and pitavastatin did (Figure 2), although valsartan is not listed as clinical substrate for OATP1B (https ://www.fda.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies Both GCDCA-3G and GDCA-3G were screened in vitro as substrates of various human liver solute carriers individually transfected into Human Embryonic Kidney (HEK) 293 cells as previously described. 37 In this instance, however, additional uptake studies were conducted with OATP1B1*5 and OATP1B1*15 similarly transfected into HEK293 cells (provided by Yuichi Sugiyama, Tokyo University, Japan), and OATP1B1*14 transfected into HEK293 cells (acquired from Absorption Systems, Exton, PA). OATP1B1*1A expressed in HEK293 cells was prepared in-house as described in Supplemental Methods.…”
Section: Discussionmentioning
confidence: 99%
“…Sample processing and bioanalysis of rosuvastatin, taurocholic acid, metformin, fluvastatin, and cyclic guanosine monophosphate has already been described. 37 Both GCDCA-3G and GDCA-3G (~ 0.01 to 100 µM) were also studied as in vitro inhibitors of OATP1B1*1A, OATP1B3, and OATP2B1 (expressed in HEK293 cells) using rosuvastatin (0.5 µM) as substrate. Where possible, the concentration of glucuronide rendering 50% inhibition of rosuvastatin uptake (IC 50 ) was determined.…”
Section: Discussionmentioning
confidence: 99%
“…However, the remaining uptake clearances of PTV and RSV in the presence of rifamycin SV (30 μM) showed no declining trend (Table I ). Of note, the recent studies reported that the complete inhibition of active influx transporters (both OATP1Bs and non-OATP1B transporters) in hepatocytes requires the rifamycin SV concentrations of 1 mM or higher ( 15 , 19 ). Thus, the measured uptake clearances of PTV and RSV in the presence of rifamycin SV (30 μM) likely include the uptake clearance via active influx by non-OATP1B transporters as well as passive diffusion.…”
Section: Discussionmentioning
confidence: 99%